Cultivating change: Reflections on the changing role of the School Head in effective implementation of the Competency-Based Curriculum in Hwange Rural Primary Schools. - Shoko, Donald (2020)
This study is on the role of the School Head in effective implementation of the competency-based curriculum in rural primary schools in Hwange District. Study objectives were: to explore the roles and responsibilities of school heads as curriculum leaders; to determine how school heads manage curriculum change for effective curriculum implementation; to establish resources that must be available to ensure effective curriculum implementation in schools; and to proffer strategies that can be employed for effective implementation of the new competency-based curriculum at school level in Zimbabwe. The study employed a qualitative approach. The questionnaire was the major instrument for data collection. Findings were that the School Head plays and has critical roles necessary for effective implementation of the competency-based curriculum in a school; effective implementation of the curriculum compels the School Head to establish synergies with all stakeholders; most schools have a critical staff and material resources shortages which compromises effective implementation of the curriculum and that challenges encountered in the implementation of the curriculum in schools require School Heads to be situational and premeditated in their effort to address them. The study recommends that Schools be adequately supported with human and material resources for effective implementation of the competency-based curriculum in Zimbabwe; teachers as curriculum implementers be continuously staff developed to meet the demands of the competency-based curriculum; avail funds for continuous professional development of teachers trained prior to implementation of the curriculum so as to enhance their professional competencies; further research be carried out in urban primary schools to establish opportunities and challenges encountered in the implementation of the competency-based curriculum in the entire Zimbabwean education system.